Bangun Sepeda Listrik Roda Tiga Dengan Sistem Hybrid Panel Surya Baterai Untuk Transportasi Inklusif - Moh Bima Fahrosyid Rizki Abdillah; Ferly Isnomo Abdi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The increasing use of fossil-fuel-powered vehicles has led to high carbon emissions and air pollution, making it necessary to develop more environmentally friendly and inclusive transportation options. This study aims to design and build a three-wheeled electric bicycle with a solar panel–battery hybrid system as an efficient, stable, and accessible transportation alternative for a wide range of users. The research method employed was Research and Development (R&D), which included the design, assembly, functional testing, and vehicle performance analysis phases. The developed system utilizes a 650 W BLDC motor, a 48 V 20 Ah Sealed Lead Acid (SLA) battery, and a 200 Wp flexible monocrystalline solar panel as an additional energy source. Testing was conducted in three speed modes—Eco, Medium, and Sport—as well as battery charging tests using the solar panel while the vehicle was stationary. The results showed that Eco mode produced the highest average range of 54.4 km, followed by Medium mode at 46.2 km and Sport mode at 38.5 km. Additionally, charging the battery using the solar panel in a horizontal position took an average of 333 minutes. The results of the study show that the solar panel–battery hybrid system is capable of effectively supporting the operation of electric bicycles and providing a more environmentally friendly, energy-efficient, and inclusive transportation alternative.